PEMBROLIZUMAB-INDUCED HYPOPHYSITIS WITH CENTRAL DIABETES INSIPIDUS: A RARE IMMUNE-MEDIATED ADVERSE EVENT - Bahrudin, Mohd Fyzal; Sarvanandan, Tharsini; Hee, Nicholas Ken Yoong (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND With the growing use of immune checkpoint inhibitors, hypophysitis is gaining increased clinical recognition while remaining a formidable diagnostic and therapeutic challenge. Pembrolizumab, a PD-1 inhibitor, is a breakthrough therapy that enhances the immune system’s attack on tumours but comes with the risk of immune-related adverse events. CASE We report the case of a 65-year-old male undergoing pembrolizumab treatment for renal cell carcinoma who presented with profound lethargy 18 months after treatment initiation. Hormonal evaluation upon admission revealed panhypopituitarism, characterized by critically low random cortisol (<14 nmol/L), ACTH deficiency (<5 pg/mL), and biochemical findings suggestive of secondary hypothyroidism (TSH: 1.68 mIU/L [0.55–4.78], free T4: 10.7 pmol/L [11.5–22.7]). The gonadal function was preserved (testosterone: 21.5 nmol/L; LH: 5.5 IU/L [1.5–9.3]; FSH: 15.8 IU/L [1.4–18.1]), while prolactin levels were mildly elevated (315 mIU/L). The autoimmune screening was ANF positive but only with titre 1:80, normal anti-dsDNA, and normal C3C4 and tumour markers were unremarkable. The patient was promptly initiated on intravenous hydrocortisone, followed by a tapering regimen of oral hydrocortisone and thyroxine replacement. Shortly after glucocorticoid initiation, he developed polyuria and polydipsia. Further evaluation confirmed cranial diabetes insipidus (DI), with low urine osmolality (101 mOsm/kg) and elevated serum osmolality (287 mOsm/kg). Subcutaneous desmopressin was initiated, leading to rapid symptom resolution and stabilization. A pituitary MRI showed no evidence of adenoma or stalk enlargement. Although pembrolizumab-induced hypophysitis is a known immune-related adverse event, arginine vasopressin (AVP) deficiency remains a rare complication of checkpoint inhibitor therapy. CONCLUSION This case highlights the spectrum of pembrolizumab-induced hypophysitis, which can manifest as panhypopituitarism and, in rare cases, cranial diabetes insipidus. Clinicians should maintain a high index of suspicion for hypophysitis in patients with new-onset fatigue post-ICI therapy, as timely hormonal replacement is crucial in preventing life-threatening adrenal insufficiency and associated complications.